2018
DOI: 10.1111/jcmm.13762
|View full text |Cite
|
Sign up to set email alerts
|

BDNF: mRNA expression in urine cells of patients with chronic kidney disease and its role in kidney function

Abstract: Podocyte loss and changes to the complex morphology are major causes of chronic kidney disease (CKD). As the incidence is continuously increasing over the last decades without sufficient treatment, it is important to find predicting biomarkers. Therefore, we measured urinary mRNA levels of podocyte genes NPHS1, NPHS2, PODXL and BDNF, KIM‐1, CTSL by qRT‐PCR of 120 CKD patients. We showed a strong correlation between BDNF and the kidney injury marker KIM‐1, which were also correlated with NPHS1, suggesting podoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Strong associations exist between BDNF and the kidney injury molecule (KIM-1), and BDNF has been recently proposed as a biomarker for glomerular injury. 37 As such, the relative downregulation of BDNF in DCD grafts might indicate that the glomerular injury is less in DCD than in DBD grafts.…”
Section: Il6 Tnfα Rankl (Tnfsf11) Cebpβ Ticam1mentioning
confidence: 99%
“…Strong associations exist between BDNF and the kidney injury molecule (KIM-1), and BDNF has been recently proposed as a biomarker for glomerular injury. 37 As such, the relative downregulation of BDNF in DCD grafts might indicate that the glomerular injury is less in DCD than in DBD grafts.…”
Section: Il6 Tnfα Rankl (Tnfsf11) Cebpβ Ticam1mentioning
confidence: 99%
“…Unique genes from our data that are associated with the filtration barrier or cytoskeleton of podocytes include the genes CX3CL1 [37], DNM3 [38], DPP4 [39] and NRX1 [40]. Unique genes from our data that are associated with podocyte function or survival include BDNF [41], CXCL16 , [42] GRIA3 [43], PDGF-C [44], RAB3A [45] and VEGF-C [46]. Members of Semaphorin gene family SEMA3A and SEMA3C were also significantly upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study demonstrated that BDNF is required for glomerular development, morphology, and function, and the expression of BDNF and KIM-1 is highly correlated in urine cells of CKD patients. Therefore, BDNF mRNA in urine cells could serve as a potential prognostic biomarker for CKD [ 203 ]. Some studies demonstrated that H 2 S reversed the decrease in TrKB receptors against chronic unpredictable mild stress (CUMS)-induced hippocampal oxidative stress, demonstrating the critical role of neurotrophic signaling in the antidepressant effects mediated by H 2 S [ 204 ].…”
Section: H 2 S As a Signaling Mediator In The Kmentioning
confidence: 99%